SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS ON ADOPTION OF DIGITAL PAYMENTS - Gaur, Parul; saxena, Ankit (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Digital payments have become very popular nowadays just to the fact that they are able to process the business transactions without cash. While there are no comprehensive researches that integrate bibliometric analysis with a systematic literature review (SLR) around the area of digital payments, there are many studies underway. This study is intended to review and analyze existing literature on electronic payments both through peer-reviewed publications and open-access data. The research is based on 835 publications from the Scopus database that cover the period of 2000 to 2023. The dataset includes 494 journal articles, 303 conference papers, 26 review papers, and 12 conference reviews. The study utilizes bibliometric techniques, systematic literature review methods, and visualization tools such as VOSviewer to ensure a comprehensive analysis. The current state of digital payments is quite unclear in the research literature. By providing the structure of the ongoing research on digital payments, this study is of great value that will help the future researchers in the conduction of qualitative literature reviews more efficiently.